Escuela de espalda para la prevención de problemas de columna vertebral en los estudiantes de 5to 6to 7mo año de educación general básica de la Unidad Educativa “Carlos Cisneros Riobamba “2017-2018. - María Auxiliadora, Broncano Cabezas (2018)
The present research is about the back pain, being the most frequent problem arnong the, it occurs in adults, but also in children even with the same prevalence, in addition, it is one of the most frequent cause for which the patient receives medical attention when a patient has back pain in childhood or adolescence is more likely to have it in adulthood, for this reason these problems must be identified on time and establish a treatment to prevent future aggravations.(Rosero Narvaez, 2014) The most common cause of back pain is a lack harmony in the muscular contractions of the components of the back, these in turn are caused by misuse due to inadequate real estate, desks, all this brings as a consequence pain that aggravate the pathology. (Gonzales Montesinos 2000). One of the concerns of educational authorities and health, parents and professionals from different sectors, is the incorrect use of school backpack and its impact on the skeletal muscle system, especially in the back. Doubts aboaut the safety and health of scholl children due to the use of backpack extend all over the world, as show by studies carried out in other coubtries in Europe, Asia, the united states and the awareness of numerous associations an entities. In this context, the American Academy of Pediatrics (AAP) and the Americaan Association of Physioterapist (APTA) offer a series of recomnendations on the correct postion of the back in scholls in order to prevent of musculoskeletal injuries